ON THE CORRELATION BETWEEN PROFESSIONAL STANDARDS AND FEDERAL EDUCATIONAL STANDARDS OF HIGHER EDUCATION - Vasily S. Senashenko (Высшее образование в России, 2016)
The work discusses the correlation between professional standards and federal educational standards for higher education. The author highlights the complexity of the problem of modification of educational standards and educational programs of higher education on the basis of professional standards.